Effectiveness of Scalp Acupuncture for Parkinson’s Disease: A Systematic Review and Meta-analysis of Randomized Controlled Trials - Junyeop Oh; Jihoon Kong; Jeonghoon Lyu; Tae Han Yook; Beom Yong Song; Yoomin Choi; Jong Uk Kim (Journal of Acupuncture Research, 2025)
The present study aimed to synthesize the findings of studies examining the effects of scalp acupuncture in the treatment of Parkinson's disease (PD). Specifically, this study sought to evaluate the efficacy of scalp acupuncture as a therapeutic modality for PD, with the goal of guiding clinical practices and research initiatives. A literature search on the following databases was conducted to identify clinical trials examining the effect of scalp acupuncture on PD: PubMed, EMBASE, CENTRAL, CNKI, KISS, RISS, KMBASE, OASIS, and ScienceON. Quantitative evidence from randomized controlled trials (RCTs) was systematically reviewed, and the study's methodological quality was evaluated using Cochrane's Risk of Bias tool. Meta-analysis was performed using Review Manager 5.3 (Cochrane Collaboration). The systematic review incorporated 15 RCTs comprising 991 participants. A meta-analysis of seven studies demonstrated that the patients treated with scalp acupuncture and Western medicine exhibited significant symptom improvements as compared with those receiving Western medicine alone. The methodological quality of the RCTs was assessed as low. Scalp acupuncture demonstrates potential as a complementary treatment to Western medicine for PD patients. Increased emphasis on conducting high-quality RCTs is crucial to assess the efficacy of scalp acupuncture in managing PD symptoms.